Prescription and Dispensing of Benzodiazepines in Times of the Covid-19 Pandemic in Brazil. - Azevedo Ferreira, Davi; Francisco da Silva, Pedro Ithalo; Florêncio de Azevedo, Maria Renata; Ricardo de Sousa, Jaelson Rodrigo; Wanderlei de Azevedo, Regina Lígia (Revista de Pesquisa: Cuidado é Fundamental)
Objective: the objective was the prevalence of prescription and dispensing of benzodiazepines in Brazilian capitals, in the first quarters of 2020 and 2021, considering the Coronavirus desease-2019 (COVID-19) pandemic. Methods: this is an epidemiological, exploratory, quantitative, documentary and retrospective study that investigated data from the National Controlled Protocol Management System. Descriptive statistics and association tests were used for data analysis, using the Software Statistical Package for Social Sciences program. In addition, the calculation of the prevalence of dispensation was performed. Results: dispensing of alprazolam and clonazepam is more prevalent. The Southeast region has the highest prevalence of dispensing (1st quarter of 2020 n = 7098.74; 1st quarter of 2021 n = 6849.77), followed by the South (1st quarter of 2020 n = 5939.6; 1st quarter of 2021 of 2021 n =5616.16). Conclusion: therefore, there was no significant increase to say that the prescription and dispensing of benzodiazepines between the years analyzed.